1975
DOI: 10.1088/0031-9155/20/3/002
|View full text |Cite
|
Sign up to set email alerts
|

Skin temperature over an artificial heat source implanted in man (applied to IR thermography)

Abstract: The medical application of infrared thermography makes use of the skin temperature as an indication of an underlying pathological process. In order to study the relation between the heat production from a source in living tissue and the overlying skin temperature, artificial heat sources were implanted subcutaneously in human volunteers. The experimental results show that a detectable surface temperature increase over the heat sources presupposes high power output or superficial implantation. The effect of for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 14 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…Additional experimental agreement is observed in an experiment (Nilsson 1975, p 377) that used human forearms. It was found that W is independent of T a (at 17 • C and 23 • C) and that an increase of h eff (air flow rate at 0 and 2 m s −1 ) causes a decrease of W. The decrease of W observed in the experiment is larger than that shown in figure 10(b) because the values of D used in the experiment are less than the default value of the current study.…”
Section: Discussionmentioning
confidence: 58%
“…Additional experimental agreement is observed in an experiment (Nilsson 1975, p 377) that used human forearms. It was found that W is independent of T a (at 17 • C and 23 • C) and that an increase of h eff (air flow rate at 0 and 2 m s −1 ) causes a decrease of W. The decrease of W observed in the experiment is larger than that shown in figure 10(b) because the values of D used in the experiment are less than the default value of the current study.…”
Section: Discussionmentioning
confidence: 58%
“…Most of the earlier studies emphasized on the study of skin temperature around heat sources for tumor diagnose [76][77][78], which is based on observations of Lawson [79] that the skin temperature over a malignant tumor is higher than that of surrounding skin due to increased blood flow in tumor.…”
Section: Skin Bioheat Transfermentioning
confidence: 99%
“…Silicon tube A spherical titanium heat source with a central temperature measuring thermistor and a heat coil was developed for implantation in animals and man (FIGURE 1). 6 The electrical leads to the heat source were encapsulated in a silicon tube. The heat sources were implanted in a passive state and allowed to heal in the desired location.…”
Section: Tltanium Heat Sourcementioning
confidence: 99%